Evaluación a nivel laboratorio del comportamiento de cuatro píldoras de material de control de pérdida de circulación para yacimientos naturalmente fracturados (2016)
In this project, it’s proposed to evaluate at laboratory level the behavior of four lost control material pills for naturally fractured reservoirs, this project will be validate through lab tests. The degree work consists first of all of a theory part where the lost circulation generalities are described, followed of a description of the circulation control mechanisms, immediately is performed a description of the four selected pills and the conventional pill taken as a reference in order to a later comparison. Once the materials used are described, it's continued with a description of the lab tests performed; Pressure Plug Test (PPT), the tests to determine the Particle Size Distribution (PSD), such as the CILAS analysis and the SEM analysis.